Broad Spectrum of Hepatocyte Inclusions in Humans, Animals, and Experimental Models. Issue 4 (22nd October 2013) - Strnad, Pavel; Nuraldeen, Renwar; Guldiken, Nurdan; Hartmann, Daniel; Mahajan, Vineet; Denk, Helmut; Haybaeck, Johannes
Abstract: We focus on hepatic inclusions, which are defined as intracellular aggregates of stainable substances. They represent established hallmarks of their respective human disorders, but unlike aggregates found in neurodegenerative disorders are often not well studied. Hepatic inclusions can be subdivided into primary liver aggregates and aggregates found in multiple tissues. The former ones consist of inclusions found in endoplasmic reticulum storage diseases such as α 1‐antitrypsin aggregates or ground‐glass hepatocytes, p62‐containing (Mallory‐Denk bodies and intracellular hyaline bodies) and porphyrin‐containing inclusions. p62‐containing aggregates are not restricted to the liver but are found in multiple other disorders such as Parkinson or Alzheimer disease. Inclusions such as pale bodies or intracellular hyaline bodies are typical for malignant disorders while others (ground‐glass hepatocytes and α1‐antitrypsin aggregates) are predominantly seen in non‐neoplastic tissues. The inclusions, which are not restricted to the liver, are often due to a systemic viral infection, but also due to disruption of glycogen metabolism or systemic inclusion‐forming diseases such as polyglutamine disorders or sarcoidosis. Despite their heterogeneity, inclusions share several pathogenic principles such as an imbalance between protein damage/misfolding on one side and repair/degradation on the other side. This is why hepatic aggregates represent a valuable tool to study the aggregation process in general and to improve our understanding of inclusions found in multiple human disorders. © 2013 American Physiological Society. Compr Physiol 3:1393‐1436, 2013.